åˆ©ç”¨è”æƒ³æ³•æé«˜ABDI AGAPE ä¸ä¸“äºŒå¹´çº§å¦ç”Ÿçš„æ±‰å—è®¤è¯»èƒ½åŠ› - Baiti, Nur; Ina, Ina; Lusi, Lusi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe Chinese character is a Chinese written form, it is an important forming structure in Chinese lessons of foreign students. According to the students who learn the second language, the Chinese characters are the parts that must also be mastered. In addition, Mandarin characters are difficult to recognize, remember and Â write. In this case, to help students understand Chinese characters, the writer carries out a research about The use of association method to improve Abdi Agape studentsâ€™s skill in recognizing chinese character. After comparing Â pre-test and post-test, the researcher found that the use of association method could improve studentsâ€™ ability in understanding Chinese characters.Keyword : Chinese Character, Association Method, Recognizing Chinese Character